Laser-Driven Single-Step Synthesis of Monolithic Prelithiated Silicon-Graphene Anodes for Ultrahigh-Performance Zero-Decay Lithium-Ion Batteries - Kothuru, Avinash; Daffan, Gil; Patolsky, Fernando (Nano-Micro Letters, 2026)
Silicon-based anodes offer a promising alternative to graphite in lithium-ion batteries (LIBs) due to significantly higher energy density. However, their practical application is limited by substantial volume expansion during lithiation, which causes structural instability and continuous formation of the solid electrolyte interphase (SEI), drastically reducing initial coulombic efficiency (ICE) and capacity retention. Strategies such as silicon nanostructuring and integration with conductive carbon matrices help accommodate volume changes and improve conductivity but fall short in fully addressing lithium loss and long-term capacity fade. Prelithiation can mitigate these issues by compensating for lithium loss and stabilizing the SEI. However, conventional prelithiation methods are complex, air-sensitive, multi-step, and ex situ, often requiring reactive lithium metal or exotic lithium salt precursors. In response, this study introduces a laser-driven, solid-state, ambient, in situ prelithiation method performed concurrently with the synthesis of silicon-graphene pseudo-monolithic composite anodes. A ternary blend of phenolic resin, silicon nanoparticles (SiNPs), and common lithium salts, subjected to rapid, low-power laser irradiation, produces a self-standing, air-stable, prelithiated composite, where the resulting porous and conductive matrix encapsulates the SiNPs, while the unique laser-induced environment triggers in situ reactions that prelithiate the silicon surface and form stable covalent interfaces. The resulting lithiated anodes reveal remarkable features, delivering over 1700 mAh g−1 with negligible capacity decay (< 2%) over 2000 + cycles at 5 A g−1, 83% retention after 4500 cycles, and ICE above 97% versus non-lithiated counterparts. The anodes also display ultrafast charging capabilities, retaining up to 63% of their maximum capacity at 10 A g−1. This innovation not only advances the development of next-generation LIBs, but also establishes a framework for converting readily available and cost-effective precursor materials into high-performing electrodes, promising to reduce complexity and costs in battery manufacturing. Highlights: 1 We report an ambient single-step laser-driven process that simultaneously synthesizes and integrates prelithiated silicon nanoparticles into a robust graphene matrix using simple precursors. 2 Prelithiation is achieved in situ through interfacial solid-state reactions between Si and common lithium salt precursors during the ultrafast photothermal graphitization of phenolic resin. 3 Prelithiated silicon nanoparticles/laser-induced graphene anodes exhibit exceptional cycling stability (> 98% capacity retention after 2000 cycles) and near-zero performance decay in Li-ion half and full cells compared to non-lithiated counterparts.